Flow through heterogeneous geological media - Yeh, T. C. (T.-C. Jim); Khaleel, Raz (Raziuddin); Carroll, Kenneth C. (Cambridge : Cambridge University Press, 2015)
This textbook integrates classic principles of flow through porous media with recently developed stochastic analyses to provide new insight on subsurface hydrology. Importantly, each of the authors has extensive experience in both academia and the world of applied groundwater hydrology. The book not only presents theories but also emphasizes their underlying assumptions, limitations, and the potential pitfalls that may occur as a result of blind application of the theories as'cookie-cutter' solutions. The book has been developed for advanced-level courses on groundwater fluid flow, hydraulics, and hydrogeology, in either civil/environmental engineering or geoscience departments. It is also a valuable reference text for researchers and professionals in civil/environmental engineering, geology, soil science, environmental science, and petroleum and mining engineering.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Groundwater flow -- Mathematical models; Porous materials -- Permeability -- Mathematical models; Transport theory -- Mathematical models